Steamboat JOHN C. BARR navigating backwards through the east channel of Five Fingers Rapids, Yukon River, ca. 1898 - Curtis, Asahel, 1874-1941 (1898)
Photographs taken by Asahel Curtis during his trip to the Klondike in 1897-1899. Caption on image: Curtis 976 Handwritten on verso: John C. Barr going down 5 Fingers backwards PH Coll 519.976 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number